Role of Trimetazidine in Ameliorating Endothelial Dysfunction: A Review - Yusof Kamisah; Hamat H. Che Hassan (MDPI AG, 2024)
Endothelial dysfunction is a hallmark of cardiovascular diseases, contributing to impaired vasodilation, altered hemodynamics, and atherosclerosis progression. Trimetazidine, traditionally used for angina pectoris, exhibits diverse therapeutic effects on endothelial dysfunction. This review aims to elucidate the mechanisms underlying trimetazidine's actions and its potential as a therapeutic agent for endothelial dysfunction and associated cardiovascular disorders. Trimetazidine enhances vasodilation and hemodynamic function by modulating endothelial nitric oxide synthase activity, nitric oxide production, and endothelin-1. It also ameliorates metabolic parameters, including reducing blood glucose, mitigating oxidative stress, and dampening inflammation. Additionally, trimetazidine exerts antiatherosclerotic effects by inhibiting plaque formation and promoting its stability. Moreover, it regulates apoptosis and angiogenesis, fostering endothelial cell survival and neovascularization. Understanding trimetazidine's multifaceted mechanisms underscores its potential as a therapeutic agent for endothelial dysfunction and associated cardiovascular disorders, warranting further investigation for clinical translation.